A simple model to predict the probability of a peach (Prunus persicae) tree bud to develop as a long or short shoot as a consequence of winter pruning intensity and previous year growth. - Daniele Bevacqua; Michel Génard; Françoise Lescourret (PLoS ONE, 2012)
In many woody plants, shoots emerging from buds can develop as short or long shoots. The probability of a bud to develop as a long or short shoot relies upon genetic, environmental and management factors and controlling it is an important issue in commercial orchard. We use peach (Prunus persicae) trees, subjected to different winter pruning levels and monitored for two years, to develop and calibrate a model linking the probability of a bud to develop as a long shoot to winter pruning intensity and previous year vegetative growth. Eventually we show how our model can be used to adjust pruning intensity to obtain a desired proportion of long and short shoots.